DEWEY'S PROPOSED TEACHING METHODOLOGY IN THE CONTEXT OF ECE - Mohd Nazri Bin Abdul Rahman; LI HANFEI (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This article explores the teaching methods proposed by Dewey in the context of early childhood education (ECE), focusing on their impact on teacher assessment and evaluation. The study also examines challenges such as balancing structured evaluations with the dynamic and flexible nature of Dewey's pedagogy, and suggests strategies to support teachers in implementing and reflecting on this approach effectively.